Comparing the Traditional and Combined Methods of Teaching Neuroantomy - Ahmadali Ghanbari; Bahram Samadirad; Vahab Ghanbari; Fereidoun Ashrafian (Tabriz University of Medical Sciences, 2013)
Introduction: The sectional neuroanatomy due to its great importance in identifying the internal structure of the brain seems to be a necessary course of study to the residents of the neurosurgery, neurology and neuroradiology. The aim of this study was to determine the effectiveness of the traditional and the combined methods of teaching the neuroanatomy to two separate groups of neurosurgery residents. Methods: At the Imam Reza hospital of the Tabriz University of the medical sciences, the efficacy of the traditional and the combined methods of teaching the neuroanatomy to two separate groups of neurosurgery residents was compared and assessed by final exams and using questionnaires. Results: The scores of the group B in a quite similar exam were higher than the group A. The questionnaire investigation also indicated that the combined method of teaching was more effective than the traditional method. Conclusion: This study also concluded that plus the traditional method of teaching the neuroanatomy, the direct observation of the serially sectioned slices of the human embalmed brain and comparing them concurrently with the similar slices of the MRI images, can raise the ability of the trainees to identify the internal structures of the brain more precisely in their medical experiences.